"Are You Sure, Sweetheart, That You Want to Be Well?": The Politics of Mental Health and Long-Suffering in Toni Cade Bambara's The Salt Eaters - Waller-Peterson, Belinda (Religions, 2019)
In analyzing the woman-centered communal healing ceremony in Toni Cade Bambara's The Salt Eaters, this article considers how these types of womb-like spaces allow female protagonists to access ancestral and spiritual histories that assist them in navigating physical illnesses and mental health crises. It employs Bell Hooks' Sisters of the Yam: Black Women and Self-Recovery alongside Arthur Kleinman's definition of illness as social and transactional to demonstrate that the recognition of illness, and the actualization of wellness, necessitates collective and communal efforts informed by spiritual and cultural modes of knowledge, including alternative healing practices and ancestral mediation.